Green Economy-Based Sustainable Innovation: A Managerial Perspective on Addressing Environmental Challenges - Nur Aini Anisa aini; Ria Dini Apriliasari; Rika Liftiana (CV Pena Jaya Pers, 2026)
Purpose: This study aims to explore how the adoption of green economy principles encourages sustainable innovation from a managerial perspective in addressing environmental challenges. Specifically, the study investigates how managers formulate strategies, allocate organizational resources, and implement environmentally responsible business practices to achieve sustainability while maintaining organizational competitiveness. The research also seeks to identify the opportunities and barriers encountered during the implementation of green economy initiatives and to understand how managerial decision-making contributes to long-term environmental and business performance. Design/methodology/approach: This study employs a qualitative research design using a multiple case study approach. Data were collected through semi-structured interviews with managers and business owners who have implemented green economy practices in their organizations, supported by direct observations and document analysis. The participants were selected using purposive sampling based on their experience in sustainable business management. Data were analyzed using thematic analysis, involving data coding, categorization, and theme development to identify managerial strategies, implementation processes, challenges, and best practices related to sustainable innovation. Triangulation of data sources and member checking were conducted to enhance the credibility and trustworthiness of the findings. Findings: The findings indicate that managerial commitment is a critical driver of sustainable innovation within the framework of the green economy. Organizations that integrate environmental considerations into strategic decision-making demonstrate greater innovation in product development, resource efficiency, waste reduction, and environmentally friendly operational processes. The study also reveals that organizational culture, stakeholder collaboration, and leadership support significantly influence the successful implementation of green economy practices. However, several challenges remain, including limited financial resources, inadequate technological capabilities, regulatory uncertainty, and low environmental awareness among some stakeholders. Despite these obstacles, organizations adopting green economy strategies experience improved operational efficiency, stronger competitive advantage, enhanced corporate reputation, and increased long-term sustainability. These findings highlight the importance of managerial capability in transforming environmental challenges into opportunities for sustainable business innovation. Research limitations/implications: This study is limited by its qualitative design and relatively small number of case organizations, which may restrict the generalizability of the findings to other industrial sectors or geographical contexts. The research focuses primarily on managerial perspectives, while the views of employees, customers, policymakers, and other stakeholders are not comprehensively explored. Future studies are encouraged to employ mixed-method or quantitative approaches involving larger samples across different industries and countries to validate and extend the proposed managerial framework. Additionally, longitudinal research could provide deeper insights into the long-term impact of green economy practices on organizational sustainability and innovation performance. Originality/value: This study contributes to the growing body of literature on sustainable innovation by integrating green economy principles with managerial decision-making in addressing environmental challenges. Unlike previous studies that predominantly examine technological or policy aspects of the green economy, this research emphasizes the strategic role of managers in fostering sustainable innovation within organizations. The findings provide both theoretical and practical insights into how managerial capabilities, leadership commitment, and organizational strategies facilitate environmental sustainability while enhancing business competitiveness. The study also offers a conceptual reference for managers and policymakers seeking to promote sustainable business transformation through green economy practices.